Long and Short Vowel Sounds in “Gasoline” and “Colors” Song Lyrics by Halsey - Rosalinah, Yanti; Alya, Wulansari Regina Shafa; Yasmin, Zahra (Manunggal Halim Jaya, 2025)
This study uses a phonetic technique to analyze the vowel sounds in Halsey's “Gasoline” and “Colors” songs. The use of long and short vowels in the lyrics is the subject of the examination. The study aims to present research findings on the long and short vowels in Halsey’s songs “Gasoline” and “Colors.” The writer also determines the impact of long and short vowels on the songs. The research methodology is a qualitative approach. The writer uses phonetics studies to analyze the long and short vowel sounds displayed in a table to provide a thorough understanding of the vowel sounds in the lyrics. According to the study, Halsey's songs' emotional effect is greatly influenced by phonetics, particularly long and short vowels. There are 87 examples of long vowels and 49 of short vowels. In the song